The Effect of Reproductive Health Educational Media on Adolescent Girls' Understanding of Normal and Abnormal Vaginal Discharge (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Vaginal discharge (leukorrhea) is one of the most common reproductive health problems experienced by adolescent girls. While vaginal discharge can be a normal physiological occurrence, it may also indicate pathological conditions when accompanied by symptoms such as itching, unpleasant odor, or changes in color and consistency. The lack of adequate knowledge among adolescents regarding the differences between normal and abnormal vaginal discharge can lead to misinterpretation of symptoms, delayed medical consultation, and increased risk of complications. Adolescence is a critical period for instilling appropriate reproductive health knowledge, making early education essential. This study aimed to determine the effect of reproductive health educational media on adolescent girls' understanding of normal and abnormal vaginal discharge. A pre-experimental method with a one-group pretest-posttest design was employed. The research sample consisted of 30 female students selected through purposive sampling. Data collection was conducted using questionnaires distributed before and after the educational intervention. The intervention consisted of leaflet and video media, both containing concise yet comprehensive information about the characteristics, causes, prevention, and treatment of vaginal discharge. The results showed an increase in the mean understanding score from 54.6 in the pretest to 78.3 in the posttest. Statistical analysis using the paired t-test produced a p-value of 0.000 (<0.05), indicating a statistically significant effect of the educational media on participants' knowledge. This finding highlights that visual and printed media, when designed appropriately, can effectively enhance reproductive health literacy among adolescents. In conclusion, reproductive health educational media are effective tools for improving adolescent girls’ understanding of normal and abnormal vaginal discharge. Strengthening health education programs in schools, particularly with engaging and accessible media, is recommended to promote early detection and prevention of reproductive health problems.